THE FUTURE OF DATA COLLECTION IN PALLIATIVE CARE PRACTICE. Issue 1 (1st March 2015) - Witt, J; Brown, A; Kaler, P; Pannell, C; Murtagh, FEM
Abstract : Introduction: Patient-reported outcome measures (PROMs) are usually completed on paper. Laptops, electronic (e/)tablets and smartphones are rarely used with palliative care patients and it is not known whether their use is feasible and acceptable in this population. Aim(s) and method(s): We explored whether palliative care patients find the use of e/tablets for PROMs data collection feasible and acceptable. To do this, we embedded a qualitative component within a larger study in two urban UK hospitals. We asked patients who completed PROMs on e/tablets or paper to complete a brief structured telephone survey followed by a semi-structured discussion of any issues experienced. Additionally, research nurses who supported patients during completion were interviewed. Results: Ten patients (70% male; age range 33–87; 30% non-cancer diagnosis) and two research nurses took part. Satisfaction with either format was high, and most found both easy to read, use and navigate. Emerging themes highlighted advantages and drawbacks of each format: Those who used paper valued the simplicity and familiarity of this format. Those who used e/tablets particularly liked the immediate transfer of their responses to electronic records and their clinician. However, several issues with e/tablets were also raised, including poor responsiveness to touch, connectivity problems and weight. Conclusion(s): E/tablet use is feasible and has potential to improve collection and use of PROMs by clinicians. However, for maximum utility, e/tablets need to be touch responsive, well connected, and lightweight, and integrated into clinical databases with real time feedback. Funder: the National Institute for Health Research—Programme.